Mapping interaction quality for nursing and medical students in primary care placement in municipal emergency care units: a systematic observational study - Giske, Solveig; Gamlem, Siv M.; Kvangarsnes, Marit; Landstad, Bodil J.; Hole, Torstein; Dahl, Berit Misund (Frontiers in Medicine, 2024)
Primary care placement for nursing and medical students is vital for developing the competence to accommodate the increasing number of patients with multimorbid and complex conditions. Prior studies have suggested that interaction quality in primary care placement empowers learning. However, research mapping interaction quality in primary care placements in municipal emergency care units is lacking. This study aimed to systematically map interaction quality for nursing and medical students in primary care placement in two municipal emergency care units.This study adopted a systematic descriptive observational design. Systematic observations (n = 201 cycles) of eight nursing students (n = 103 cycles) and six medical students (n = 98 cycles) were used to map interaction quality across six learning situations between March and May 2019. Observations were coded using the Classroom Assessment Scoring System -Secondary. Data were analyzed using descriptive statistics and Spearman correlations.Interaction quality is described in three domains: (I) emotional support, (II) framework for learning, and (III) instructional support, and the overall measure, student engagement. The results indicated middle-quality interactions in the emotional and instructional support domains and high quality in the framework for learning domain and student engagement. Correlations exhibited similar patterns and ranged from non-significant to strong correlations.The interaction qualities indicated a generally positive and supportive learning environment contributing to nursing and medical students' learning and active participation in work tasks related to their professional roles. Thus, this new form for primary care placement for nursing and medical students at the municipal emergency care units was found to be a positive learning arena. These results may enhance nursing and medical education programs in countries with similar health services and education. Health education, supervisors, peers, and others contributing to students' learning should recognize which interaction qualities may affect learning and how to improve quality, thus affecting supervisors' approach to training students. While the CLASS-S showed potential for mapping interaction qualities for nursing and medical students in primary care placement in municipal emergency care units, further studies are needed to validate the CLASS-S for use in clinical placement settings.